Hypothetical Learning Trajectory for Eighth Graders' Understanding of Pythagorean Theorem through Ethno-Realistic Mathematics Education Assisted by Video - Farida Nursyahidah; Muhtarom Muhtarom; Irkham Ulil Albab; Maya Rini Rubowo; Windia Hadi (Department of Mathematics Education Program IPI Garut, 2025)
Pemahaman konsep geometri, terutama yang berkaitan dengan teorema Pythagoras, seringkali menjadi kendala bagi siswa. Artikel ini bertujuan untuk mengembangkan lintasan belajar hipotetis mengenai materi teorema Pythagoras dengan pendekatan Pendidikan Matematika Etno-Realistik Jawa (E-RME). Penelitian dilakukan dengan menggunakan metode penelitian desain yang meliputi tiga tahap utama, yaitu perancangan awal, pelaksanaan eksperimen pembelajaran, dan analisis retrospektif. Penelitian ini melibatkan siswa kelas VIII di salah satu SMP di Kota Semarang. Fokus artikel ini adalah pada tahap perancangan awal, yaitu dihasilkan hipotesis lintasan belajar yang meliputi tiga kegiatan utama: (1) mengamati konteks video rumah Joglo untuk menentukan jenis segitiga berdasarkan besar sudutnya dan konsep segitiga istimewa; (2) menemukan konsep teorema Pythagoras dan menentukan jenis segitiga berdasarkan panjang sisinya; (3) menerapkan teorema Pythagoras. Hipotesis lintasan pembelajaran ini layak untuk diujicobakan pada tahap eksperimen pembelajaran untuk membantu siswa membangun pemahaman yang lebih mendalam tentang konsep-konsep teorema Pythagoras, sekaligus menumbuhkan apresiasi terhadap budaya lokal dan keragaman dalam berpikir matematika menggunakan E-RME. Understanding of geometric concepts, especially those related to the Pythagorean theorem, is often an obstacle for students. This study aims to develop a hypothetical learning trajectory for the Pythagorean theorem material using the Javanese Ethno-Realistic Mathematics Education (E-RME) approach. The research was conducted using the design research method, which includes three main stages: initial design, implementation of learning experiments, and retrospective analysis. This research involved grade VIII students in one of the junior high schools in the city of Semarang. The focus of this study is on the initial design stage, resulted a learning trajectory hypothesis which includes three main activities: (1) observing the video context of the Joglo house to determine the type of triangle based on the size of its angles and the concept of special triangles; (2) discovering the concept of the Pythagorean theorem and determining the types of triangles based on the length of their sides; (3) applying the Pythagorean theorem. This learning trajectory hypothesis is worth testing at the experimental stage of learning to help students develop a deeper understanding of the concepts underlying the Pythagorean theorem, while simultaneously fostering an appreciation of local culture and diversity in mathematical thinking through E-RME.